2020
DOI: 10.3390/chemosensors8040110
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Active Compounds Quantity from Pharmaceuticals Based on Ginkgo biloba

Abstract: Ginkgo biloba is one of the most important sources of active compounds, mainly flavonoids and phenolic compounds. Due to its importance related to pharmaceutical practice, the making of a qualitative and quantitative method for the detection and quantification of active compounds from Ginkgo biloba pharmaceutical products is desirable. In this study, the content of biological active compounds from Ginkgo biloba products was estimated using cyclic voltammetry. The electrochemical determination of active compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…anti-carcinogenic effects, nephroprotective activity against kidney injury induced by cisplatin and its hepatoprotective activity against "nonalcoholic fatty liver disease", antiinflammatory activity [26][27][28] Genista tinctorial Currently, many publications related to the study of the antioxidant properties of individual representatives of polyphenols are presented in the literature [8][9][10][11][12][13]. However, no articles were found that included the study of a number of natural coumarins and flavonoids using integrated approaches such as those presented in this work.…”
Section: Genista Tinctorialmentioning
confidence: 99%
See 2 more Smart Citations
“…anti-carcinogenic effects, nephroprotective activity against kidney injury induced by cisplatin and its hepatoprotective activity against "nonalcoholic fatty liver disease", antiinflammatory activity [26][27][28] Genista tinctorial Currently, many publications related to the study of the antioxidant properties of individual representatives of polyphenols are presented in the literature [8][9][10][11][12][13]. However, no articles were found that included the study of a number of natural coumarins and flavonoids using integrated approaches such as those presented in this work.…”
Section: Genista Tinctorialmentioning
confidence: 99%
“…AOs in the human body can be classified into three types of reactions in terms of their chemical transformation. Accordingly, the mechanisms of antioxidant action can be divided into three types: the electron transfer (ET-mechanism), the proton transfer (HAT-mechanism), and the mechanism of complex-in the process of research Currently, many publications related to the study of the antioxidant properties of individual representatives of polyphenols are presented in the literature [8][9][10][11][12][13]. However, no articles were found that included the study of a number of natural coumarins and flavonoids using integrated approaches such as those presented in this work.…”
Section: Genista Tinctorialmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential range was selected from −2 to +2 V. The voltametric curve shows anodic peak −1.3, 0.8 V in the forward scan, the cathodic and anodic peaks observed 1.3, −0.8, 0.3 V in the reverse scan is indicated quasi electrochemical process. The cathodic and anodic peak currents observed were found to be reduced with electrolysis 33 …”
Section: Resultsmentioning
confidence: 96%
“…Therefore, by comparing the results obtained by the three spectrophotometric methods and taking into account those obtained by electrochemical methods (CV and DPV), we can obtain information about the redox properties and radical scavenging activity induced by electron and hydrogen transfer [ 97 ] not only in the case of catechin alone, but also in the case of its determination in various nutraceutical products.…”
Section: Resultsmentioning
confidence: 99%